Meta-Analysis: Effectiveness of SSRIs vs SSRIs in conjunction with CBT in treating depression in young adolescents - Kresnia, Gabriele Mustika; Hasuki, Winda; Pradana ratnasari, Nanda Rizqia (Indonesian Journal of Life Sciences, 2020)
Objective: To compare the efficacy of SSRI medication alone and SSRI+CBT combined. Methods: NCBI Pubmed, DARE, CSDR and NGC were searched October-November 2019. The population size, as well as the base and endpoint CGAS mean and standard deviation from the three studies included, are recorded. Statistical analysis was done in RStudio with the "meta" package. Results: For the SSRI only, the effect size was -1.82 with a 95% confidence interval between -2.28 and -1.37. For the SSRI and CBT combined, the effect size was -1.68 with a 95% confidence interval between -2.39 and -0.98. The effect size for both SSRI and SSRI + CBT didn't cross the null effect line, but the heterogeneity exceeds 50%. The result for the comparison of post SSRI vs. SSRI + CBT showed the effect size of -0.05 with a 95% confidence interval between -0.23 and 0.12. The size effect did cross the null effect line, but the heterogeneity was less than 50%. Conclusion: Both methods were shown to be effective. However, due to statistical inconsistencies, it couldn’t be concluded whether the combination of SSRI and CBT is better than treatment with SSRI alone.